29Si NMR and SAXS investigation of the hybrid organic–inorganic glasses obtained by consolidation of the melting gels. Issue 11 (6th March 2017) - Jitianu, Andrei; Cadars, Sylvian; Zhang, Fan; Rodriguez, Gabriela; Picard, Quentin; Aparicio, Mario; Mosa, Jadra; Klein, Lisa C.
Abstract : This study is focused on structural characterization of hybrid glasses obtained by consolidation of melting gels. Abstract : This study is focused on structural characterization of hybrid glasses obtained by consolidation of melting gels. The melting gels were prepared in molar ratios of methyltriethoxysilane (MTES) and dimethyldiethoxysilane (DMDES) of 75%MTES-25%DMDES and 65%MTES-35%DMDES. Following consolidation, the hybrid glasses were characterized using Raman, 29 Si and 13 C Nuclear Magnetic Resonance (NMR) spectroscopies, synchrotron Small Angle X-Ray Scattering (SAXS) and scanning electron microscopy (SEM). Raman spectroscopy revealed the presence of Si–C bonds in the hybrid glasses and 8-membered ring structures in the Si–O–Si network. Qualitative NMR spectroscopy identified the main molecular species, while quantitative NMR data showed that the ratio of trimers (T) to dimers (D) varied between 4.6 and 3.8. Two-dimensional 29 Si NMR data were used to identify two distinct types of T 3 environments. SAXS data showed that the glasses are homogeneous across the nm to micrometer length scales. The scattering cross section was one thousand times lower than what is expected when phase separation occurs. The SEM images show a uniform surface without defects, in agreement with the SAXS results, which further supports that the hybrid glasses are nonporous.